Pengukuran Konsumsi Makanan Ibu Hamil Trimester III di Pukesmas Kenjeran Kota Surabaya - Ari Susanti (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2017)
Caloric needs in third trimester pregnant woman will increase for fetal growth and placenta. The older age of the pregnancy so the more energy are needed. Third trimester pregnant women require an additional 300kcal of energy from the recommended amount of sufficiency for Indonesians (Permenkes, 2013). Data in Indonesia showed only 14.0% of pregnant women with sufficiency energy level ≥100% Energy sufficiency rate (AKE) both in urban and rural (Kemenkes RI, 2014). This study aims to describe the level of food consumption in pregnant women trimester three at Kenjeran Primary Health Care. This research used descriptive approach with population of pregnant mother of trimester III as manya as 35 people and sample as many as 30 respondents with simple random sampling technique. The survey method used is a repeated 24-hour recall and food frequency questionnaires. Result : The results showed that 66.7% of respondents with deficit status of energy consumption and only 10% of respondents have good energy consumption status. Recommendations can be given in this study were health workers should be willing to provide nutrition education to pregnant women. Define guidelines for adequate food for pregnant women so they can be used by pregnant women as a reference in determining the ingredients of food consumption appropriately. Keyword: Pregnant woman, Measurement of Food Consumption, repeated 24-hour recall, food frequency questionnaires.